GAMBARAN KEBERSIHAN GIGI DAN MULUT SERTA KETERAMPILAN MENYIKAT GIGI PADA SISWA KELAS IV SDN 7 DAUH PURI - Elynda Nurfaizah Martin; Ni Made Sirat (Jurnal Kesehatan Gigi (Dental Health Journal), 2018)
Dental and oral health is influenced by several factors, one of them is the precision of brushing teeth. The correct behavior in brushing teeth between 10-14 years old childrens in Bali, it’s only around 4,1%. This data shows thah the behavior of oral and dental maintenance in children stiil at very low level. This research is a descriptive study that intends to explain the level of dental and oral hygiene as well as tooth brushing skills for all students at 4 thgrade SDN 7 Dauh Puri.This research use total population of 80 peoples and the data that has been collected consist of primary and secondary data. The result showed that the level of dental and oral hygiene with good criteria is about 18 students, 58 students quite criteria, and four students have bad criteria. The average level of oral and dental oral hygiene index of fourth  degree SDN 7 Dauh Puri is 1.62 with quite criteria.The results showed that students who be have that brushing with very good criteria as many as 20 students, 42 students have good criteria, the criteria quite as much as seven students, and there are 11 students includes criteria who need guidance. There are 33 student who have quite criteria of dental and oral hygiene with brushing teeth skills criteria good.